A novel G isolated from Drosophila constitutes a visual G protein subunit of the fly compound Eye. - Schulz, S.; Huber, A.; Schwab, K.; Paulsen, R. (Journal of Biological Chemistry, 1999)
Visual transduction in the compound eye of flies is a well established model system for the study of G protein-coupled transduction pathways. To characterize key components of the phototransduction cascade we performed substractive hybridization screening. We cloned the cDNA coding for the visual Ggamma (Ggamma(e)) subunit from Drosophila which had so far eluded identification at the molecular level. Northern blot analysis revealed the presence of a major, 1.4-kilobase(kb) Ggamma(e) transcript and two minor transcripts of 1.8 and 6 kb in size. The major 1.4-kb mRNA is expressed preferentially in the eye. The spatial expression pattern determined for Ggamma(e) as well as co-immunoprecipitation experiments demonstrated that Ggamma(e) dimerizes with Gbeta(e) to form the heterodimeric Gbetagamma subunit which functions in visual transduction in the Drosophila compound eye. Ggamma(e) shares common characteristics with the visual Ggamma subunits of human rod and cone photoreceptors although different classes of Galpha subunits are employed in vertebrate and invertebrate phototransduction. By the molecular cloning and characterization of the visual gamma subunit of Drosophila one of the few missing links in the well studied Drosophila phototransduction cascade has been characterized to complete our knowledge about the Drosophila visual transduction pathway.